The Effect of Brand Experience on Brand Loyalty with The Mediation of Brand Love and Brand Trust - Khairullah; Puspaningrum , Astrid; Yuniarinto, Agung (The International Journal of Accounting and Business Society, 2025)
Purpose - to be able to recognize the importance of brand loyalty in recent decades as markets have become more globally competitive and to secure brand position in an industry. Design/methodology/approach - This research uses quantitative methods. The data in this study were obtained through distributing online questionnaires to 120 respondents who became the sample because during the study there was a covid-19 pandemic which limited meetings with respondents directly. Data analysis using structural equation modeling partial least square (SEM-PLS) with the Smart-PLS 3.0 application. Findings - The results showed that brand experience, and brand trust have a significant effect on brand loyalty. However, brand love has no significant effect on brand loyalty. This study also shows that brand love and brand trust mediate the effect of brand experience on brand loyalty. Practical implications - The results of the study can be used for evaluation of related parties, namely the Tehbotol Sosro company in facing increasingly sharp competition in the RTD tea industry, gaining consumer loyalty and of course increasing company revenue. Originality/value - This research contributes to consumer responses in the Malang area with the object of Tehbotol Sosro. The results of this study can also be used as a reference for studies related to RTD Tea brand loyalty to brand experience through brand love and brand trust. The research results also provide input to the managerial of Tehbotol Sosro.